Enhanced visualization of fine needles under sonographic guidance using a MEMS actuator - Shen, Zhiyuan (2018)
Localization of a needle tip is important for biopsy examinations in clinics. However, the needle tip is sometimes difficult to discern under the guidance of sonography due to its poor visibility. A mini actuator that radiates a low-intensity ultrasound wave was manufactured using micro-electro-mechanical system (MEMS) technology. Interference between the radiated and diagnostic ultrasound pulses was observed as bright lines in the B-mode ultrasound image, from which the mini actuator could be recognized with ease. Because the distance between the mini actuator and the needle tip is fixed, the needle tip can be determined despite its inconsistent appearance in the sonography. Both gel phantom and ex vivo tissue evaluation showed that the needle tip can be determined reliably utilizing the acoustic interference pattern.